Analysis of a novel CuCl2 back contact process for improved stability in CdTe solar cells. (21st May 2019) - Artegiani, Elisa; Menossi, Daniele; Shiel, Huw; Dhanak, Vin; Major, Jonathan D.; Gasparotto, Andrea; Sun, Kai; Romeo, Alessandro
Abstract: One of the crucial points in the production of CdTe solar cells is the insertion of copper in the back contact and in the absorber. As demonstrated by the top performing devices presented in literature: copper is necessary for high efficiency devices. However, despite this, copper was found to be a fast diffuser degrading the cell in the long term. Different approaches for limiting this effect have been widely presented from several laboratories, from the preparation of Cux Te by the controlled evaporation of Cu and Te to the application of ZnTe, which incorporates Cu, blocking its diffusion in the bulk. We have developed a wet deposition method for inserting in the CdTe structure a quantity of copper equivalent to a 0.1‐nm‐thick Cu layer. We are able to reach similar efficiencies to the ones of devices with a standard 2‐nm‐thick evaporated copper layer, but with a dramatic improvement in performance stability. Abstract : As demonstrated by the top performing CdTe devices, Cu is necessary for high efficiency. However, it is a fast diffuser degrading the cell in the long term. We have developed a novel CuCl2 wet deposition method to insert minimal amount of Cu in the CdTe. This brings to high efficiencies but with a rollover‐free ohmic back contact and a dramatic improvement in performance stability.